THE ECONOMIC VALUE OF FOREST ECOSYSTEM SERVICES - APSALYAMOVA, Saida Olegovna; KHASHIR, Bella Olegovna; KHUAZHEV, Oleg Zakireevich; TKHAGAPSO, Murat Baizetovich; BGANE, Yuri Kazbekovich (Journal of Environmental Management and Tourism, 2016)
Payment for ecosystem services (PES) is the payment made by the user of environmental services, such as the purification of water, to landowners who provide this service. The real existence of PES requires to clearly identifying the user and supplier, as well as a number of other necessary conditions on the basis of summarizing the information available in the sources existing today. Particular attention is paid to the way in which these conditions can now be created in forest management in the region. Many case studies are devoted to forest environmental services, which address best practices in promoting the introduction of PES. This study contains a comprehensive discussion of the implications of PES for politics and public relations, and recommendations mention the need of a clear understanding of when PES can be a useful tool for the purposes of the transition to "green" economy and when it is more expedient to use other methods.
Keywords: biodiversity; ecosystem; environmental; forest policy and services; green economy; payment for ecosystem services; tourism